Rethink education and skills in outdoor education: "on the door" approach emerging from Dolomiti-Unesco project - Chiara Urbani; Andrea Guaran (Firenze University Press, 2024)
The achievement of socio-political goals of ecological transition goes through the qualification of education and training systems and teacher expertise. The Dolomiti-Unesco project describes a school training experience that involved both teachers and students in outdoor education activities and explorative experiences in natural environment of Dolomite territories. The reflection on the course undertaken has fostered the emerging of an "on the door" approach which rejoin indoor and outdoor in methodology and educational training, supporting their qualification and improvement. This allows us to rethink the capability to affect bottom-up on change system and influence educational and training policies. Furthermore, it outlines new workable directions to actualize the sustainability of social and civil communities that are truly involved, responsible and capable to build a personal and social agency able to create future changes.   Ripensare formazione e competenze nell'outdoor education: l'approccio "on the door" emergente dal progetto Dolomiti-Unesco. L'attuabilità di obiettivi politico-sociali di transizione ecologica passa per la qualificazione dei sistemi d'istruzione e formazione e della professionalità docente. Il progetto Dolomiti-Unesco illustra un'esperienza di formazione nelle scuole che ha coinvolto docenti e studenti in attività di outdoor education ed esperienze esplorative nell'ambiente naturale entro il territorio dolomitico. La riflessione sul percorso intrapreso ha contribuito a far emergere un approccio "on the door" che coniuga indoor e outdoor nella metodologia e nella formazione contribuendo al loro miglioramento e qualificazione. Questo consente di ripensare la capacità di incidere bottom-up sul cambiamento di sistema e influenzare le politiche formative. Inoltre, tratteggia nuove direzioni da intraprendere per rendere attuabile la sostenibilità di comunità sociali e civili realmente coinvolte, responsabili e capaci di costruire un'agency individuale e collettiva in grado di generare cambiamenti futuri.